Covalent-bonded graphyne polymers with high hardness - Hu, M.; He, J.; Wang, Q.; Huang, Q.; Yu, D.; Tian, Y.; Xu, B. (Сверхтвердые материалы, 2014)
Eight covalent-bonded graphyne polymers have been proposed using the newly developed USPEX and CALYPSO methods based on the first principle calculations. These polymers are energetically more favorable than the corresponding graphyne under ambient pressure, and seven of them are more stable than fullerene C₆₀, indicating their existence possibilities. The mechanical and dynamic stabilities of these crystal structures have been confirmed by calculating their elastic constants and phonon dispersion curves, respectively. The newly developed variable-cell nudged elastic band (VC-NEV) simulations show that the graphyne → polymer transformation exhibits lower energy barrier than the graphite → diamond transformation. Two of the graphyne polymers have been found to be superhard, and the others are hard materials. These graphyne polymers possess tunable electronic properties from metallic to semiconductive.